Tartuffe - Molière,Bedford, Brian (Bloomsbury, 2015)
Initially banned in France by King Louis, Molière's celebrated social satire Tartuffe exposes false piety and hypocrisy in the Catholic Church. When a pious fraud worms his way into a wealthy family and manipulates the patriarch into giving up his fortune, it's up to his family to expose the truth before they end up in the poorhouse!
10.5040/9781580817783.01
Keywords: Clergy; Radio plays; French; Audiobooks